Morphology of antennae of Dendroctonus vitei (Coleoptera: Curculionidae: Scolytinae), with special reference to sensilla clustered into pit craters. Issue 4 (1st June 2018) - López, María Fernanda; Armendáriz-Toledano, Francisco; Albores-Medina, Arnulfo; Zúñiga, Gerardo
Abstract: As reported recently by the authors, the third and fourth antennomeres of the antennal club of the bark beetle Dendroctonus vitei Wood (Coleoptera: Curculionidae: Scolytinae) possess conoid sensilla clustered inside spherical or bulb-shaped invaginations of the cuticle that resemble geological pit craters. These structures are novel relative to other Dendroctonus Erichson species examined. The morphology and ultrastructure of different sensilla types on the antennal club and within the pit craters of D. vitei are herein described in detail with the aid of light, environmental scanning electron, and transmission electron microscopy. Five types of sensilla were found: fluted, basiconica type I, and trichodea types I, II, and III. The pit craters were composed of clusters of multiporous sensilla basiconica arising from the inner surface of the concavities, and the morphology and ultrasructure of these sensilla are consistent with an olfactory function. The presence of pit craters in the D. vitei on the anterior side of the antennal club is an diagnostic character for this species and an autapomorphy of great taxonomic importance within the Dendroctonus frontalis Zimmermann species complex.